Reestruturação produtiva e condições de trabalho - um estudo dos trabalhadores da indústria de fiação e tecelagem de algodão de Campina Grande - Paraíba - Andrade, José Cristovão de (2001)
This research is the result of an interest in studying the changes introduced in the process of restructuring of production. These changes include the reorganization of production ,through the introduction of new technology, the decentralization of production through sub-contracting, and the adoption of new management models at the administrative level . Special attention has been paid to the consequences of these changes on the workers with reference to their working conditions. In other words, the effects of these transformations on the workers have been analyzed. The following firms in the textile sector in the municipality of Campina Grande, PB were chosen to carry: out this study : CIRNE. SALUTE and TÊXTIL. The choice of the spinning and weaving branch was due to the fact that this sector has the greatest number of functions connected to the preparation of threads and fibers. Another reason for the choice was the fact that some firms are being subjected to changes , though many of these changes are outdated in relation to those being adopted in other firms belonging to the same area in Campina Grande and other cities in the Northeast. CIRNE and SALUTE, two of the firms included in this study, have been subjected to important changes in the areas of production and administration. However, the third firm under study. TÊXTIL, has continued to maintain the traditional system of production and organization. Thus. it has been possible to observe with greater clarity the effects of the changes on workers in both situations. Several visits were made to specialized organs in order to gain a better knowledge of this sector of production. The information obtained helped to make choices. Besides interviews with the directors of the firms and the directors of trade unions. 49 semi-structured interviews were also carried out. In these interviews . priority was given to questions which would not only provide objective data to identify the subjects, but also convey images and evocations of their apprehensions about the conditions of work to which the workers were submitted. The objective of this study having been the profound investigation of these questions, theoretical reflections on the theme by the following authors have been studied : ANTUNES (1995), ANDERSON (1996). ALVES (1999), BIHR (1998), CATTANI (1997), DIAS (1996) , FERNANDES ( 1995). HARVEY (1996). LEITE (1994) . MARX (1996). MATTOSO ( 1998) . and POCHMANN ( 1998). The study of these and other authors made it possible to understand better the process of restructuring of production and its repercussions on the situation of workers in the textile sector in Campina Grande. The results obtained revealed that the restructuring process in the firms under study was slow and that the investment in technology was very low in comparison to other regions in the country. Working conditions were precarious for both men and women. Salaries were low, working hours long , and the rhythm of work intensified. There were no opportunities for promotion. There was a high rate of rotation in the work-force. The educational level of the workers was low. Directors and supervisors were rigid about discipline. The working environment was unhealthy. It was observed that these problems profoundly affected the organization of labor unions. There were few members , scheduled activities did not have credibility , mobilization was difficult and the workers were afraid to participate in events. Data revealed that both men and women were equally affected, thus proving untrue the hypothesis that men were more affected because of the increase of the number of women in the work-force. The changes which have occurred in the fields of technology and organization have caused both men and women to face similar problems with regard to availability of jobs, and in the conception and execution of work in the textile sector in Campina Grande. In this context, it can be observed that the restructuring process in the firms CIRNE, SALUTE and TEXTIL has aggravated the precarious working conditions and also affected the organization of labor unions.